Development and assessment of the health-related quality of life scale for children with hearing loss in China - Jie Liu; Yu-Xiao Wang; Jing Li; Dahong Wu; Guang-xian Zeng; Jing Cheng; Jia-yi Wang; Jian-Zhong Zheng; Lu He (BMC Public Health)
Abstract Background Hearing loss significantly affects children’s lives; however, the health-related quality of life (QoL) of children with this disability is not well measured. We sought to develop a reliable and valid measure of health-related QoL in children with hearing loss. Methods We constructed a conceptual framework to assess the QoL of children with hearing loss based on the Pediatric Quality of Life Inventory™ Version 4.0 child quality of life scale and World Health Organization Quality of Life Brief Version disability general version. The item pool was generated through two rounds of the Delphi method and subsequent group discussions. Subsequently, both a pre-survey and a formal survey were administered across eight hospitals and nine special education schools located in Shanxi and Hebei Province, China. The process of selecting items was grounded in classical test theory and item response theory. Ultimately, we assessed the reliability and validity of the QoL Scale designed for children with hearing loss in China.x` Results The final health-related QoL scale for children with hearing loss (HRQOL-CHL) included 37 items, 6 domains, and 8 subdomains. Reliability assessment encompassed Cronbach’s alpha coefficient, split-half reliability, and retest reliability measures. Specifically, for the entire scale, Cronbach’s alpha yielded a coefficient of 0.755, binary reliability of 0.796, and retest reliability of 0. 931. The validity findings indicated that the scale performed as anticipated. Both exploratory factor analysis and confirmatory factor analysis demonstrated that this multidimensional scale was well-suited for assessing children with hearing loss, demonstrating a superior fit. Conclusions The HRQOL-CHL exhibits positive reliability, validity, and feasibility, which makes it an efficient QoL assessment tool for children with hearing loss in China.